Neutriinojen ja kvarkkien sekoitusmatriisien välinen yhteys - Jukkala, Henri (2012)
In this thesis relations between neutrino mixing matrix and quark mixing matrix are studied. The focus of the analysis is on two simple cases. In the first case it is assumed that the left matrix that diagonalizes the mass matrix of charged leptons and the corresponding matrix of down quarks are equal. In the second case it is likewise assumed that the corresponding diagonalizing matrices of neutrinos and up quarks are equal.